EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KECERDASAN EMOSIONAL PADA PESERTA DIDIK KELAS XI DI SMAN 5 CIMAHI - Kustiana, Refina Latifah Juni; Rohaeti, Euis Eti; Pahlevi, Reza (IKIP Siliwangi, 2024)
Emotional intelligence is an individual's ability to manage emotional problems with the intelligence they have and can maintain the expression of their emotions well. Individuals who are emotionally intelligent can be seen from how these individuals understand their emotions, are able to manage their emotions well, are able to motivate themselves, are sensitive to others and can build good relationships with others. The purpose of this study was to test the effectiveness of group counseling services using role playing techniques in increasing the emotional intelligence of class XI students at SMAN 5 Cimahi. This study uses a quantitative approach. The research method used was a quasi-experimental non-equivalent control group design in the experimental group and the control group. Data was collected using an emotional intelligence questionnaire referring to Goleman's theory. The sample for this research was students of class XI at SMAN 5 Cimahi who were selected through a random sampling technique. The data was then analyzed using the N-gain score and obtained an average score of 71.3% in the experimental group which was in the